THE FOURTH INDUSTRIAL REVOLUTION AND THE LEADERSHIP OF THE FUTURE - García Vega, Silvia (2020)
Times has changed; the world has changed; and the way of managing organizations and people too. The stage of the socioeconomic history that we have to live today has been called the fourth Industrial Revolution. In it, new technologies have invaded inevitably and have led us to change, almost obligatorily, the way we work and relate to our family, work team, clients and environment.